Sample reading lesson plans for grade five - Soriano, Consorcia Cordova 1932- ([Quezon City s.n.], 1967)
The study illustrates the reading lesson plans for gradual psychological unfolding approach, dimensional ordinary approach, dimensional remedial approach, exercises in making inferences, and exercises in outlining for the improvement of reading in the elementary and high school.
Thesis (M.A.T. Reading)--University of the Philippines
Keywords: Reading; Lesson planning; Reading (Elementary).